WAR Field Spying Robot - Vikhram, Rajaa; Sundeep, Jamili; Teja, N; Raghu Sai Nadh Reddy, K; Sundeep, J (International Journal of Engineering and Technology, 2018)
On aiming to increase the safety because by using this robot we can know their activities by keeping some safe distance from the enemy, the flexibility of attacking will be increased because we can know their activities and there will be a laser that will lock the position of the enemy and guides the missal, this is also contain the metal detector that will helpful in detecting the land mains which will lead to death, and control of this robot will be very easily done because it is controlled wirelessly and by connecting to Bluetooth of any android mobile. We have done this project for our army to detect the land mains safely and for the safety of our soldiers and to attack them without keeping our army soldiers life on the line.Â Â